AGRO-ECONOMIC SYNERGY: ENHANCING FOOD SECURITY THROUGH INNOVATIVE AGRICULTURAL PRACTICES IN AZERBAIJAN - Hijran Ismayilova; Sona Hajiyeva (Agora International Journal of Economical Sciences)
This paper examines the critical role of agro-economic synergy in enhancing food security in Azerbaijan. Amid global challenges such as climate change, population growth, and economic uncertainty, Azerbaijan has significant potential to modernize its agricultural sector through innovative practices like precision agriculture, biotechnology, and sustainable farming techniques. The research highlights the country's strategic initiatives, including the "State Program for Ensuring Food Safety in the Republic of Azerbaijan for 2019-2025," which emphasizes the integration of technological advancements and economic strategies to boost agricultural output while reducing environmental impact. By employing a qualitative methodology based on secondary data from governmental and global organizations, the study explores how advanced agricultural practices can improve both food availability and export potential. Case studies such as the development of agroparks and partnerships with international institutions further demonstrate Azerbaijan's efforts to modernize its food systems and achieve long-term sustainability. Despite facing infrastructural and policy challenges, the paper underscores the importance of continued innovation and investment to secure food sovereignty and strengthen Azerbaijan’s position in global markets. The findings contribute to a broader understanding of how agricultural modernization can drive economic growth while ensuring food security.